Relevansi Pandangan Falibilisme dalam Filsafat Matematika Terhadap Pendidikan Matematika Abad Ke-21 - Putri, Hilda Abelia Waluyo; Kusuma, Anggun Badu (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to examine the relationship between the perspective of fallibilism and mathematics learning in the 21st century. The method used is a literature review, with data sources consisting of 11 scientific articles published between 2021 and 2025. The articles were obtained through searches using the Publish or Perish tool and the Google Scholar database, with keywords "fallibilism", "philosophy of mathematics", and "21st-century mathematics education". The data collection process involved selecting articles based on relevance criteria. The collected data were then analyzed qualitatively using content analysis techniques, focusing on identifying main themes and the interconnection of concepts. The analysis results are presented in two main tables depicting the integration of philosophy, curriculum, and technology in mathematics learning, and active learning strategies that align with the principles of fallibilism. The study's findings indicate that fallibilism views mathematics as knowledge that develops socially and is open to revision. This perspective is in line with contemporary educational principles that emphasize the importance of critical thinking skills, reflective thinking, and mastery of numerical literacy. Additionally, technology-based learning approaches such as Project-Based Learning and Problem-Based Learning are considered suitable with the principles of fallibilism because they encourage the exploration of ideas, problem-solving, and active student participation.